Alienation and Power in Doris Lessing’s The Fifth Child (Raparin Journal of Humanities (RJH), 2023)
In her novel "The Fifth Child", Doris Lessing illustrates the rigidity of a patriarchal society. The analysis of masculinity in this study shows that society as a whole, in addition to its criminal subcultures, are maintained by the masculine law and order, which encourages prejudice against those who do not fit into the norms of society, believe in authoritarian social systems, and favor rational solutions to moral judgments. Therefore, Lessing has fostered the complexities of social relationships between husband and wife from various socioeconomic strata in terms of a crippled child, Ben. Her unbiased insight into the thinking of society’s underprivileged women as well as those who represent the oppressive established society sheds light on various aspects of patriarchy. For this purpose, the current study intends to investigate Lessing’s treatment of women’s alienation and power. It aims to look at psychological conflicts, social alienation, and social status and power through the art of characterization and plot construction.